Template-Directed Polymerization of Binary Acrylate Monomers on Surface-Activated Lignin Nanoparticles in Toughening of Bio-Latex Films - Wang Luyao; Wang Qingbo; Rosqvist Emil; Smått Jan-Henrik; Yong Qiwen; Lassila Lippo; Peltonen Jouko; Rosenau Thomas; Toivakka Martti; Willför Stefan; Eklund Patrik; Xu Chunlin; et al. (WILEY-V C H VERLAG GMBH, 2025)
Fabricating bio-latex colloids with core-shell nanostructure is an effective method for obtaining films with enhanced mechanical characteristics. Nano-sized lignin is rising as a class of sustainable nanomaterials that can be incorporated into latex colloids. Fundamental knowledge of the correlation between surface chemistry of lignin nanoparticles (LNPs) and integration efficiency in latex colloids and from it thermally processed latex films are scarce. Here, an approach to integrate self-assembled nanospheres of allylated lignin as the surface-activated cores in a seeded free-radical emulsion copolymerization of butyl acrylate and methyl methacrylate is proposed. The interfacial-modulating function on allylated LNPs regulates the emulsion polymerization and it successfully produces a multi-energy dissipative latex film structure containing a lignin-dominated core (16% dry weight basis). At an optimized allyl-terminated surface functionality of 1.04 mmol g(-1), the LNPs-integrated latex film exhibits extremely high toughness value above 57.7 MJ m(-3). With multiple morphological and microstructural characterizations, the well-ordered packing of latex colloids under the nanoconfinement of LNPs in the latex films is revealed. It is concluded that the surface chemistry metrics of colloidal cores in terms of the abundance of polymerization-modulating anchors and their accessibility have a delicate control over the structural evolution of core-shell latex colloids.